Teachers' digital competences: a scale construction and validation study - Aydin, Mehmet Kemal; Yildirim, Turgut; Kus, Metin (Frontiers in Psychology, 2024)
Improving teachers' digital competences is sine qua non for effective teaching and learning in today's digital society. However, there is a limited number of comprehensive and reliable scales to measure teachers' digital competences. Regarding this, the present study aimed to develop and validate a comprehensive scale to assess teachers' digital competences. Building on previous studies, a draft scale developed and piloted with a sample of teachers from all educational levels. The procedures of Exploratory Factor Analysis (EFA) were followed to refine the scale, resulting in a five-point Likert scale with 36 items loaded onto four factors. The final scale was called as Teachers' Digital Competences Scale (TDC-S). Confirmatory factor analysis (CFA) was employed to validate the fourfactor structure. Reliability analysis was performed using Cronbach's alpha (α), McDonald's omega (ω), and Composite Reliability (CR), indicating high psychometric properties. Convergent and discriminant validity analyses were also performed to assess the validity of the latent structures in TDC-S. The findings suggest that the TDC-S is a valid and reliable instrument for assessing teachers' digital competences at all grade levels from primary to high schools. It can be used to inform teacher training and development programs, and to identify teacher candidates who need additional assistance regarding improving their digital competences.